An Implementation of a Packetized Display Protocol Architecture for IRLED Projector Systems - Aaron Landwehr; Tyler Browning; Christopher Jackson; Daniel May; Andrea Waite; Hamzah Ahmed; Fouad Kiamilev (IEEE Photonics Journal, 2019)
Traditional display protocols have limitations in terms of fixed frame rates, high bandwidth requirements, and precise control over the display of frames. We propose a novel scalable packetized display protocol architecture incorporating dynamic frame rates, high speed capabilities, and dynamic synchronization to bridge performance gaps. We further provide a modular FPGA implementation of the architecture for use on array emitters.